Assessing integrated biomarkers of triplefin fish Forsterygion capito inhabiting contaminated marine water - A multivariate approach. (February 2022) - Montenegro, Diana; González, M. Teresa; Hickey, Tony; Rahnama, Mostafa; Green, Saras; Lear, Gavin
Abstract: The presence of multiple chemicals in aquatic ecosystems makes evaluation of their real impact on the biota difficult. Integrated biomarkers are therefore needed to evaluate how these chemicals contribute to environmental degradation. The aims of the present study were to evaluate responses to and effects of marine pollution using a series of biomarkers through multivariate analyses. Transcriptional responses of cyp1a (cytochrome P450), mt (metallothionein), vtg (vitellogenin) and cyp19b (cytochrome P450 aromatase); branchial and hepatic histological alterations; and Fulton condition factors (CF) were evaluated, as well as the metals and polycyclic aromatic hydrocarbons present in Forsterygion capito in Auckland, New Zealand. Sites were selected along a contamination gradient: four highly contaminated sites and four less contaminated. Molecular responses with a higher relative expression of the mt and cyp1a genes were detected at a highly contaminated site (Panmure). Several histological lesion types were found in the livers of fish inhabiting both types of sites, but gill lesions were present primarily at highly contaminated sites. In terms of general health status, the lowest CF values were overwhelmingly found in fish from the same site (Panmure). The multivariate approach revealed that telangiectasia and hyperplasia were associated with the presence of chemicals, and these showed negative associations with the CF values, with fish from three highly contaminated sites being most affected. In conclusion, the multivariate approach helped to integrate these biological markers in this blennioid fish, thus providing a more holistic view of the complex chemical mixtures involved. Future studies should implement these analyses. Graphical abstract: Image 1 Highlights: Serial of biomarkers were assessed in a blennioid fish. Organic and inorganic chemicals were evaluated. Branchial lesions were associated with chemicals. High mt and cyp1a mRNA levels were found in a highly polluted site. Multivariate method identified the most relevant stressors.